Cultural Reconstruction of the Communicative Approach at the Rumah Moderasi Beragama of Universitas Islam Negeri Sumatera Utara in the Projection of Wasathiyyah Culture - Siregar, Adnan Hasmuri; Nashrillah, Nashrillah (Journal Analytica Islamica, 2025)
This study examines cultural reconstruction through the communicative approach of the Rumah Moderasi Beragama (RMB) at the State Islamic University of North Sumatra (UINSU) in projecting the culture of wasathiyyah (moderation) within the academic environment. Motivated by the phenomenon of increasing intolerance despite the rising Religious Harmony Index, this research employs a qualitative methodology with an ethnographic approach grounded in the constructivist paradigm. Primary data were collected through in-depth interviews with five key informants, consisting of RMB administrators and students, supplemented by secondary sources such as books, scholarly articles, and academic journals. Data collection techniques included interviews, participant observation, and documentation, with informants selected using purposive sampling. Data analysis followed the Miles, Huberman, and Saldana model, encompassing stages of reduction, display, and conclusion drawing, while data validity was ensured through source triangulation. The findings reveal that RMB UINSU’s communication strategies such as curriculum integration, training programs, and the use of social media and dialogue spaces have significantly fostered the internalization of wasathiyyah values. However, the effectiveness of communication is highly dependent on the communicator’s capacity, equitable information distribution, and the alignment of messages with the audience’s moral foundations. The discussion highlights the importance of communication accommodation and moral resonance as crucial factors in successful message delivery. The study concludes that RMB UINSU has functioned as an agent of moderate religious cultural reconstruction, although there remains a need to strengthen multimodal communication strategies and expand outreach to less-engaged student communities.